Islamic Boarding Curriculum Management Innovation Entrepreneurship Al-Maun Muhammadiyah School (Pesantren S-PEAM, Pasuruan City) - Achmad, Wachyudi; Iwantoro, Iwantoro (Journal of Islamic Education, 2021)
Pasuruan Indonesia S-PEAM Islamic Boarding School was established on August 18, 2015. The establishment plan was originated from the ideals of the Chairman of the Regional Government of Muhammadiyah Pasuruan City to have Islamic Boarding School as one of the cadre of Muhammadiyah's successor generation, with the hope that pesantren pioneered have a clear positioning on a national scale. Exploring the potential, skills and talents as a provision of life that is progressive, modern and entrepreneurial. While the label entrepreneur is a strategy to instill the values of entrepreneurial spirit in order to become a person who is empowered with creativity, positive thinking, high spirited, not quick to complain, not easily give up on the situation, have constructive productivity, and always think innovative to get something useful for himself and others. This research uses an action approach that aims to develop new skills for teachers by trying to find new approaches that can be applied directly and the results can be assessed easily. In this case the results of a process of students must be concrete which is not only proven by the results and achievements that are cognitive. The action research approach is very appropriate to find teacher skill development variables that can encourage the discovery of a new approach whose results can affect student outcomes. This study also seeks to find a parallel relationship between science, behavior, charity and moral action with descriptive analysis.